A pilot study of routine screening for distress by a nurse and psychologist in an outpatient haematological oncology clinic - Musiello, T.; Dixon, G.; O'Connor, Moira; Cook, D.; Miller, L.; Petterson, A.; Saunders, C.; Joske, D.; Johnson, C. (W.B. Saunders Co., 2017)
Aim: To explore the: 1) prevalence of distress, type of problems experienced by haematological patients, and referrals for supportive care; 2) effect of demographic and clinical variables on distress, and 3) effect on the time of health professionals conducting the screening in the ambulatory chemotherapy setting. Methods: Participants completed the National Comprehensive Cancer Network Distress Thermometer and Problem List and had a follow-up screening discussion with a health professional. Results: Of 68 participants, 40% reported significant distress (≥4) on the Distress Thermometer (mean 3.2, SD 2.4). All patients reported physical problems and 72% reported emotional problems—the major contributors to distress and to time spent with the health professional. Distress was unrelated to age, gender or cancer type. Patients were less likely to have significant distress at the end of treatment than at the beginning (OR = 0.15, 95% CI: 0.03; 0.72,). Forty patients (59%) were referred to supportive services. The psychologist spent less time with patients compared to the nurse (18 vs 48 min, p < 0.001). The more emotional problems reported, the greater the time spent with the patient (rs = 0.34, p = 0.009). Conclusions: Nurses can appropriately screen for distress and address significant distress reported by haematology patients undergoing chemotherapy without over burdening the nurse or patient.